PENGARUH MEDIA KINCIR PERKALIAN BERBASIS KODE QR TERHADAP PEMAHAMAN KONSEP PERKALIAN MATEMATIKA SISWA KELAS III SD - Hizbulloh Alfarisi, Salman; Susiloningsih, Wahyu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of using a QR Code-Based Multiplication Wheel media on the understanding of multiplication concepts among third-grade students at SDN Kepuhkiriman 1. The background of this research is based on students’ low understanding of multiplication, as learning activities tend to emphasize memorization rather than comprehension of multiplication as repeated addition. The QR Code-Based Multiplication Wheel is a manipulative learning medium in the form of a rotating wheel containing multiplication numbers and equipped with QR codes linked to interactive digital content, such as explanatory videos, animations, and practice exercises. This media is designed to help students understand multiplication concepts concretely through visual, kinesthetic, and digital activities. This research employed a quantitative approach using a quasi-experimental design with a Posttest-Only Control Group Design model. The research subjects consisted of two classes: class III A as the experimental group and class III B as the control group, each consisting of 25 students. Data collection was conducted through a learning achievement test in the form of multiplication concept understanding questions administered after the treatment (posttest). The data were analyzed using an independent sample t-test with the assistance of the latest version of SPSS software. The results showed a significant difference between the average posttest scores of the experimental group and the control group, with the experimental group achieving higher scores. The Sig. (2-tailed) value was less than 0.05, indicating that the QR Code-Based Multiplication Wheel media has a positive and significant effect on improving students’ understanding of multiplication concepts. This media can also serve as an innovative alternative for teachers in developing more effective and engaging mathematics learning.